An Exploration of Hotel Management Operational on Kamala Hotel Resort - Ayu Putri, Ni Komang Carrissa; Santi Diwyarthi, Ni Desak Made (Westscience Press, 2024)
This research focuses on exploring how to operate management hospitality at Kamala Hotel Resort. The study aims to know how to operate efficiently and potential implementation in the industry. The research is based on in-depth interview, observation and study literature approach with diverse departments. This analysis was used to analyze the data using previous literature on operational management. The Findings indicate that operational management is based on the skill and experience of the employee in the hospitality industry and the policy of the hotel. Moreover, the study highlights that skill and experience impact operation management in the hospitality industry. The result showed that the hotel management operational has a very important role in an hospitality industry. Hotel management operational in Kamala Hotel and Resort help college student managing all departments that have different goals, work together across departments to achieve the goal or vision of the hotel, and increase guest satisfaction, so that it can increase profit from hotels.